TINDAK TUTUR EKSPRESIF DALAM FILM PENDEK KOS-KOSAN KARYA PANIRADYA KAISTIMEWAN - Efid Winarni; Miftah Nugroho; Dwi Suryani (Jurnal Bastra (Bahasa dan Sastra), 2024)
The aim of the study is to investigate the functions and types of expressive speech acts in the short film "Kos-kosan". The research employs a qualitative descriptive approach. The research object is the short film titled "Kos-kosan". Data collection is conducted through the observation method with advanced note-taking techniques. Data analysis employs a pragmatic approach to examine the use of functions and types of expressive speech acts. A total of 44 data points are identified, encompassing various functions of expressive speech acts, including expressions of anger, mockery, complaint, blame/accusation, apology, praise, hope, and gratitude. These 44 data points are further categorized into types of direct literal speech acts and indirect literal speech acts.